2020
DOI: 10.1042/bsr20192257
|View full text |Cite|
|
Sign up to set email alerts
|

miR-802 participates in the inflammatory process of inflammatory bowel disease by suppressing SOCS5

Abstract: The present study aims to reveal the detailed molecular mechanism of microRNA (miR)-802 in the progression of inflammatory bowel disease (IBD). IBD tissues were obtained from IBD patients, followed by CD4+ cells isolation. Then, qRT-PCR and ELISA were used to detect the expression of miR-802, suppressor of cytokine signaling 5 (SOCS5), interleukin (IL)-17A and tumor necrosis factor (TNF)-α. Transfection of miR-802 mimics and miR-802 inhibitor in CD4+ cells was detected by Western blot. TargetScan and luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Moreover, miR-34a may induce increased level of IL-17 and other proinflammatory cytokines via SIRT1 direct targeting and subsequent induction of NF-κB and the downstream pathway ( Karbasforooshan and Karimi, 2018 ). Remarkably, miR-802 increases Th17 immune response by targeting the suppressor of cytokine signaling (SOCS5) in inflammatory bowel disease ( Yao et al, 2020 ). Apart from immune diseases, the relation between miRNAs and Th17 has been demonstrated in other pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-34a may induce increased level of IL-17 and other proinflammatory cytokines via SIRT1 direct targeting and subsequent induction of NF-κB and the downstream pathway ( Karbasforooshan and Karimi, 2018 ). Remarkably, miR-802 increases Th17 immune response by targeting the suppressor of cytokine signaling (SOCS5) in inflammatory bowel disease ( Yao et al, 2020 ). Apart from immune diseases, the relation between miRNAs and Th17 has been demonstrated in other pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-802 is another miRNA that has been studied in cholesteatoma. Previously, its role was confirmed in mediating the pathogenesis of a variety of tumors [108], obesity [109,110], osteoporosis [111], and inflammatory bowel disease [112].…”
Section: Microrna-802mentioning
confidence: 97%
“…Suppressor of cytokine signaling (SOCS) family members are well‐known negative regulators of cytokine‐dependent signaling. A previous study reported that miR‐802 upregulation aggravated inflammatory bowel disease by suppressing SOCS5 in a mouse model 9 . As a cytokine signaling regulator, SOCS5 is involved in the regulation of inflammatory responses and oxidative stress in chronic obstructive pulmonary disease (COPD) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that miR-802 upregulation aggravated inflammatory bowel disease by suppressing SOCS5 in a mouse model. 9 As a cytokine signaling regulator, SOCS5 is involved in the regulation of inflammatory responses and oxidative stress in chronic obstructive pulmonary disease (COPD). 10 It also plays a critical role to control several immune diseases such as allergic conjunctivitis.…”
mentioning
confidence: 99%